Thermodynamic and Transport Properties of Biomass-Derived Furfural, Furfuryl Alcohol and Their Mixtures - Zoran V. Simić (MDPI AG, 2021)
The limited reserves and well-known disadvantages of using fossil energy sources have increased the need for appropriate renewable substitutes in the production of various chemicals and materials. Biomass has been shown to be worthy of attention since it can be converted to biofuels and value-added chemicals relatively easily. The design of biomass valorisation process requires knowledge on the thermodynamic behaviour of the biomass-derived compounds, such as furfural and furfuryl alcohol. The thermodynamic and transport properties of the binary system furfural + furfuryl alcohol were studied at various temperatures and pressures. Density, speed of sound and refractive index were measured in the temperature range T = (288.15–345.15) K and viscosity was measured at temperatures up to 373.15 K, all at atmospheric pressure. Further, the density of pure components was obtained in the temperature range (293.15–413.15) K for furfural and (293.15–373.15) K for furfuryl alcohol at pressures up to 60.0 MPa. The obtained density values were correlated using the modified Tammann–Tait equation with an average absolute deviation lower than 0.009% for furfural and furfuryl alcohol. The optimised parameters were used for the calculation of the isothermal compressibility, the isobaric thermal expansivity, the internal pressure and the isobaric and isochoric specific heat capacities. The reported data are a valuable source of information for the further application of the investigated compounds.